PEDAGOGICAL FOUNDATIONS FOR THE FORMATION OF COLLECTIVIST RELATIONS IN THE STUDENT SPORTS TEAM - O‘razbayev Jakhongir Temur ugli (Journal Park Publishing, 2023)
Education in the team, for the team and through the team is one of the leading principles of the pedagogical education system, justified and confirmed by pedagogical experience. The formation of a student’s personality occurs under the influence of various types of activities, including the activities of a sports team. The formation of collectivistic relations in the process of students' sports activities has a positive effect on their attitude towards other types of activities. Student athletes are more aware of the social significance of not only sports, but also their main type of activity - educational and work.
Keywords: team, student, experience, relationships, practical activities, sports team.